Meta Analisis: Kualitas audit berdasarkan persepsi auditor eksternal Indonesia Periode 2007-2022 - Astro Yudha Kertarajasa (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
Frauds committed by external auditors (public accountants) in the country opens Indonesian citizens' insight into how the audited entity commits bribes to obtain good audit results. The different interests of business people and management make quality audits difficult to carry out. This study aims to describe state of the art research on external auditor perceptions of audit quality in Indonesia from 2007 to 2022. The research method used is meta-analysis and external auditor perceptions of audit quality as the unit of analysis in this study. Data collection techniques with documentation techniques by collecting previous studies on external auditors' perceptions of audit quality. The results of the research show that the study of external auditors' perceptions of audit quality in Indonesia began in 2007 and will continue until 2022. Meanwhile, indicators for measuring audit quality begin with auditor competence, independence and ethics as a moderation for measuring audit quality. The results showed that the most widely used measurement indicator was the independence indicator with a total of 47 studies or around 16% of the 88 journals and continued with competency indicators with a total of 36 researchers or around 13.3% of the 88 journals. The use of the same measurement indicators for audit quality will not necessarily make the results of one study the same with another. So there will be inconsistent research results.